2021
DOI: 10.24996/ijs.2021.62.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red Cabbage and Garlic Extracts on Oxidative Stress Induced by Fumonisin B1

Abstract: This study was designed to investigate the protective effects of red cabbage and garlic extracts on the oxidative stress induced through treatment with fumonisin B1 in male mice. The study was conducted on sixty male mice that were divided  randomly into six groups. Group 1included control mice, mice in group 2 received a daily oral dose (200 µg/kg.b.w) of fumonisin B1 for one month to induced mycotoxicosis, mice in group 3 received 500 mg/kg.b.w red cabbage extract plus fumonisin B1, mice in group 4 received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…The protective effect of garlic regarding oxidative processes has also been documented. Not only does garlic contribute to the decrease in ROS levels, but it also mitigates other proinflammatory parameters, such as SOD, catalase (CAT), and GPx activities [37][38][39][40]. In accordance with the previous literature, this work showed that AFB1 increased ROS production five times in comparison to the control, while the addition of garlic attenuated the effect of AFB1, resulting in similar values to the control.…”
Section: Discussionsupporting
confidence: 91%
“…The protective effect of garlic regarding oxidative processes has also been documented. Not only does garlic contribute to the decrease in ROS levels, but it also mitigates other proinflammatory parameters, such as SOD, catalase (CAT), and GPx activities [37][38][39][40]. In accordance with the previous literature, this work showed that AFB1 increased ROS production five times in comparison to the control, while the addition of garlic attenuated the effect of AFB1, resulting in similar values to the control.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies [32,33] reffered that when treated with garlic 5% increase T-AOC with decrease in MDA. Garlic extract exhibit antioxidant activities by scavenging the free radicals generated in rat kidney [34]. Also, these result agree with Ghorbel et al, [35] who have demonstrated that garlic, by its antioxidant power, has nephroprotective properties, which have been attributed to the active compound S-allyl cysteine (SAC).…”
Section: Discussionsupporting
confidence: 87%
“…The protective properties of antioxidants are caused by their capability of acting as free radical scavengers, thus protecting DNA, cell proteins, and lipids. It protects us from cancer, premature aging, diabetes, ulcer and Alzheimer's diseases [19][20][21][22][23]. Anthocyanin concentration in red cabbage is 322mg/100 g [24].…”
Section: Introductionmentioning
confidence: 99%